IMPLEMENTASI NILAI- NILAI BUDAYA DALAM KEHIDUPAN KEHIDUPAN SEHARI-HARI MASYARAKAT KAMPUNG KAJANG KELUARAHAN TAMANGAPA RAYA KEC. MANGGALA KOTA MAKASSAR - Nisa, Alifia Fakhrun; B, Muhaemin; Natsir, Nasrah (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to describe: (1) Implementation of cultural values in the daily life of the Kampung kajang community in the village of Tamangapa Raya Kec. Manggala Makassar City; (2) Knowing the extent of the efforts of the kajang village community to preserve cultural values in the village of Tamangapa Raya village Kec. Manggala. Makassar City. The research used a qualitative approach with a survey type of research. The subject of this research is the kajang village community of Tamangapa Raya village, while the object of this research is cultural values. Data collection is done by interview, observation and documentation methods. The techniques used in data analysis are data reduction, data presentation and conclusion drawing. Triangulation used to explain the validity of the data using source triangulation. Based on the results of the study, it shows that the cultural values implemented by the people of Kajang village to continue to preserve the cultural values that exist in their ancestors and with interactions in the community also have a tendency to increase the sense of solidarity as members of the community. This can be observed in everyday life.Keywords: Life Values, Community